Nursing Perspective of the Humanized Care of the Neonate and Family: A Systematic Review - Sagrario Gómez-Cantarino; Inmaculada García-Valdivieso; Mercedes Dios-Aguado; Benito Yáñez-Araque; Brigida Molina Gallego; Eva Moncunill-Martínez (MDPI AG, 2021)
This systematic review aims to determine the extent to which published research articles show the perspective of health professionals in neonatal intensive care units (NICU), as facilitators of family empowerment. Studies conducted between 2013 and 2020 were retrieved from five databases (PubMed, Cochrane, CINHAL, Scopus, and Google Scholar). The search was carried out from January to October 2020. A total of 40 articles were used, of which 13 studies (quantitative and qualitative) were included in this systematic review. Its methodological quality was assessed using the mixed methods assessment tool (MMAT). In these, the opinions and perspectives of professionals on the permanence and participation of parents were valued. In addition, the training, experiences, and educational needs of nursing within the NICU were determined. The crucial role of health professionals in the humanization of care and its effect on the neonate-family binomial was estimated. However, conceptual changes are needed within the neonatal intensive care units. To implement humanization in daily care, family participation should be encouraged in them. For this, it is necessary to modify hospital health policies to allow changes in the infrastructure that facilitate open doors 24 h a day in special services.